2008
DOI: 10.1542/peds.2007-1314
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Maternal Age and Infant Health Outcomes Among Medicaid-Insured Infants in South Carolina: Mediating Effects of Socioeconomic Factors

Abstract: Infants of adolescent mothers are more likely than infants of older mothers to use a variety of health care services that suggest poorer health. A considerable proportion of this greater use seems to be attributable to specific characteristics of mothers, such as socioeconomic characteristics, rather than to an inability that is common among adolescents to promote infant health or to use health care appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
(30 reference statements)
1
16
0
1
Order By: Relevance
“…Research conducted with the non-Aboriginal population has shown that children of teen mothers have worse health (including higher rates of low birth weight, small for gestational age, and unintentional injuries) and poorer behaviour compared to the children of older mothers (Wolfe & Perozek, 1997). However, in some studies the differences in outcomes between children of teen and older mothers are explained by differences in socio-economic factors (Pittard, Laditka, & Laditka, 2008). Children of younger mothers often live in more difficult circumstances: they are more likely to live in low-income families, have a lone parent, and have mothers who did not graduate from high school (Dahinten, Shapka, & Willms, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted with the non-Aboriginal population has shown that children of teen mothers have worse health (including higher rates of low birth weight, small for gestational age, and unintentional injuries) and poorer behaviour compared to the children of older mothers (Wolfe & Perozek, 1997). However, in some studies the differences in outcomes between children of teen and older mothers are explained by differences in socio-economic factors (Pittard, Laditka, & Laditka, 2008). Children of younger mothers often live in more difficult circumstances: they are more likely to live in low-income families, have a lone parent, and have mothers who did not graduate from high school (Dahinten, Shapka, & Willms, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize the following three relationships between the early signs of the SDT and infant mortality (we review and discuss the literature in the next section): (1) marriage postponement is negatively associated with infant death rates. On average, couples in a delayed marriage and/or parenthood would be better educated, more willing to sacrifice self-realizations and personal desire for their children, and be better prepared for a future with their children than their counterparts entering marriage and/or parenthood early (Lesthaeghe and Neidert 2006; McLanahan 2004; Pittard, Laditka and Laditka 2008). Therefore, marriage postponement would provide an environment that facilitates infant health.…”
Section: Introductionmentioning
confidence: 99%
“…Marriage postponement (and delay in childbearing) has been linked to resources for children (McLanahan 2004) and child health (Pittard et al 2008). Delayed marriage has been found to increase marital stability, which contributes to parenting quality and consequently, infant health (Martin 2004; McLanahan 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations